2001
DOI: 10.1093/condor/103.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Using Hydrogen Isotope Geochemistry to Estimate the Natal Latitudes of Immature Cooper's Hawks Migrating Through the Florida Keys

Abstract: We constructed a regression model for the relationship between stable-hydrogen isotope ratios in immature Cooper's Hawk (Accipiter cooperii) feathers (δDf) and precipitation in areas where feathers were grown (δDp) across much of the latitudinal and longitudinal extent of the species' breeding range. We used our model to estimate δDp values from δDf values of immature Cooper's Hawks captured during migration in the Florida Keys. We compared these estimated δDp values to a published map of δDp values of North A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 18 publications
3
38
3
Order By: Relevance
“…We detected an inverse relationship between latitude and dD at a relatively fine spatial scale in the upper Midwest, as was expected based on the similar larger scale trend in North America (Chamberlain et al 1997;Hobson and Wassenaar 1997;Meehan et al 2001Meehan et al , 2004. However, our dD values from South Dakota were substantially less depleted than those from other states and explained much of the latitudinal relationship.…”
Section: Discussionsupporting
confidence: 83%
“…We detected an inverse relationship between latitude and dD at a relatively fine spatial scale in the upper Midwest, as was expected based on the similar larger scale trend in North America (Chamberlain et al 1997;Hobson and Wassenaar 1997;Meehan et al 2001Meehan et al , 2004. However, our dD values from South Dakota were substantially less depleted than those from other states and explained much of the latitudinal relationship.…”
Section: Discussionsupporting
confidence: 83%
“…β  = 0.68 to 1.0: [7], [14], [16], [20], [46]. A slope of less than one implies that large differences in δD GS values across the landscape will result in only small differences in δD F values.…”
Section: Discussionmentioning
confidence: 99%
“…A similar concern over lack of population-level specificity has also begun to emerge in isotopic studies (Wunder et al, 2005). Several studies have reported that, using regression techniques based on H isotope ratios, assignment of individuals to any subset of the species' breeding range was unproductive (Kelly et al 2001, Meehan et al 2001). However, this isotopic marker has also been useful in uncovering the existence of previously unknown breeding populations (Hobson et al 2001.…”
Section: Introductionmentioning
confidence: 99%